Triple test cross analysis for yield and yield components in rice (Oryza sativa)* - RAM, T; DEEN, RAM; MISHRA, B; PADMAVATHI, G; RAMA PRASAD, A S; VIRAKTAMATH, B C (The Indian Journal of Agricultural Sciences, 2011)
The additive, dominance and epistatic components of genetic variations for yield and yield traits were analyzed using 39 triple test cross progenies derived by crossing 'IR 50', 'C 14-8' and the F, ('IR 50' x 'C 14-8') with 13 diverse varieties, resistant1 tolerant to different biotic and abiotic stresses. The estimate of total epistasis was non-significant for all the traits while partitioning of epistasis indicated the involvement of i type (additive x additive) of epistasis for plant height, number of grainslpanicle and kernel length. The magnitude of additive variance was higher than dominance for plant height, number of grains/panicle, 100- grain weight, grain yield and kernel length. While higher value of dominance variance was observed for rest of the traits. The predominance of additive and dominance type of gene action for yield and some of the important yield traits observed in the present findings can be exploited effectively following random intermating in segregating generations and selection in later generation.